Metodología para la evaluación del riesgo ambiental en el transporte de materiales y desechos peligrosos en Ecuador continental y evaluación del riesgo ambiental para el transporte de materiales y desechos peligrosos en la zona 7 del Ecuador continental que comprende las provincias del Oro, Loja y Zamora Chinchipe - Cóndor Toapanta, Luis Antonio (2016)
The goal of this work was to develop a methodology to assess environmental risks generated by the movement of hazardous materials and waste in the national land routes. On the one hand, the bibliographic information collected gave us the methods for assessing community risks (PNUMA-DTIE, 2003), and environmental laws to transport hazardous materials and waste in Ecuador. Thereby, the general information matrix elaborated is accordance with (A.M. No.026, 2008) and (INEN 2266, 2013), to identify a political-territorial space, routes, hazardous materials and waste, etc. Eventually, the components which make a part of an environmental risks, major threats and vulnerabilities of ground transport in Ecuador was identified by collection historical data created by (ANT, 2015); (MAE, 2012); (MTOP, 2015) and (SNGR, 2012). On the other hand, when the information was achieved a criteria, qualitative and quantitative ranges for assessing of threats and vulnerabilities was established to identify thought these the type of risk for certain transport route into three categories: high risk-red, medium risk- yellow and low risk- green. Finally, the methodology developed has been applied to the specific case for transporting of inorganic cyanides, which are the main hazardous wastes generated by the mining industry in the El Oro, Loja and Zamora Chinchipe provinces (Zone 7 of Ecuador).